2013
DOI: 10.5536/kjps.2013.40.1.067
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Housing Systems - Barn vs Cage on the First Phase Egg Production and Egg Quality Traits of Laying Pullet

Abstract: With an increasing concern on laying hen welfare, barn system has appeared as one of the alternatives to replace the conventional cage. This study was conducted to compare the early laying performance and egg quality at the barn system with those at the conventional cage. A total of 288 shaver-579 brown layers were used for 9 weeks (21 st to 30 th weeks of age) feeding study. Feed consumption and egg weight were significantly (P<0.01) higher at barn than at cage.However, there were no significant differences b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 14 publications
4
2
0
Order By: Relevance
“…The result of the current study agreed with the findings of Pavlovski et al (1994) and Ahammed and Ohh (2013), who found significantly higher YCS in cages than on barn. However, Pistekova et al (2006) found greater yolk color in floor than in cage, but provided no potential reason for the difference.…”
Section: Resultssupporting
confidence: 94%
See 4 more Smart Citations
“…The result of the current study agreed with the findings of Pavlovski et al (1994) and Ahammed and Ohh (2013), who found significantly higher YCS in cages than on barn. However, Pistekova et al (2006) found greater yolk color in floor than in cage, but provided no potential reason for the difference.…”
Section: Resultssupporting
confidence: 94%
“…The data given an impression that the difference in HDEP between rearing systems was statistically non significant at all ages. The result is in agreement with the findings of Jin and Craig (1988), Anderson and Adams (1994) and Ahammed and Ohh (2013).…”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations